Productivity and efficiency analysis using DEA: Evidence from financial companies listed in Bursa Malaysia - Omar Sharif; Md Zobaer Hasan; Florentina Kurniasari; Atang Hermawan; Ardi Gunardi (Management Science Letters, 2019)
This study evaluates the technical efficiency, productivity change of financial companies listed in the Malaysian stock exchange (Bursa Malaysia) and examines the effects of productivity change on efficiency over the period 2007–2016. Moreover, this study also concentrates on the ranking of financial companies according to their efficiency scores. Data Envelopment Analysis (DEA) is uti-lized on a Malmquist Productivity Index in order to calculate the financial companies’ efficiency scores. The results of this study show that some firms were fully efficient. The results implied that these companies were in optimal control of their inputs or resources to generate the maximum outputs. Also, the results indicate a tremendous productivity gain was mostly because of a positive shift in frontier technology and positive shift in technical efficiency. This study is significant because it helps to identify the efficient companies from the financial sector in Malaysia based on multiple inputs and outputs by using the DEA model. Common misspecification problems observed that instability of efficiency scores over productivity.